Analisis Kelayakan dan Faktor Usahatani Janggelan di Kawasan Hutan Pinus - susantriana dewi (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2020)
Abstract— Janggelan farming is mostly carried out under pine stands, but the feasibility of this farming has never been done, besides that, the production factors that affect farming are also unknown, so it needs research that can be used as a basis to determine the steps to be taken in farming to increase the income of janggelan farmers so that worthy of being occupied by the community around the pine forest. The purpose of this study was to determine the feasibility and production factors that affect janggelan farming in the pine forest area. The method used in this research is a survey method to collect primary data and secondary data. Data were analyzed using the F test and t test. Based on the research results, it was found that the cultivation of janggelan under pine stands was feasible. The biggest factor affecting the production of janggelan is the use of manure. Keywords—: Feasibility; farming; janggelan; pine forest.